2009
DOI: 10.1007/s00432-009-0714-1
|View full text |Cite
|
Sign up to set email alerts
|

The importance of −460 C/T and +405 G/C single nucleotide polymorphisms to the function of vascular endothelial growth factor A in colorectal cancer

Abstract: The results indicate that the two SNPs have a functional influence on the VEGF-A protein levels in normal colorectal tissue. The possible clinical implications of the findings need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…However, some researchers indicated that the results did not support an association with tumor size, histological grading, tumor stage, lymph node metastasis, and age at diagnosis in CRC cases and the contribution of each genotype to tumor characteristics might be closely related to the type of organ that carries the malignancy (Hofmann et al, 2008;Dassoulas et al, 2009). As for the VEGF -460C > T SNP, the C allele was associated with increased VEGF gene expression in CRC tissue and with increased protein concentration of VEGF in normal colorectal tissue (Yamamori et al, 2004;Hansen et al, 2010b) in contrast with our results. In the present study, there was no association for the VEGF + 936C > T and -460C > T variants in the risk of CRC (Table 2).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, some researchers indicated that the results did not support an association with tumor size, histological grading, tumor stage, lymph node metastasis, and age at diagnosis in CRC cases and the contribution of each genotype to tumor characteristics might be closely related to the type of organ that carries the malignancy (Hofmann et al, 2008;Dassoulas et al, 2009). As for the VEGF -460C > T SNP, the C allele was associated with increased VEGF gene expression in CRC tissue and with increased protein concentration of VEGF in normal colorectal tissue (Yamamori et al, 2004;Hansen et al, 2010b) in contrast with our results. In the present study, there was no association for the VEGF + 936C > T and -460C > T variants in the risk of CRC (Table 2).…”
Section: Discussionmentioning
confidence: 95%
“…Although it has been indicated that VEGF could be a good marker for determining the risk of developing CRC and could be used as a therapeutic target for new molecular anticancer drugs (Hanrahan et al, 2003;Fernando and Hurwitz, 2004;Dassoulas et al, 2009;Vidaurreta et al, 2010), the data remain conflicting if VEGF gene polymorphisms are associated with the prognosis of CRC (Yamamori et al, 2004;Park et al, 2007;Bae et al, 2008;Maltese et al, 2009;Wu et al, 2009;Hansen et al, 2010b;Antonacopoulou et al, 2012;Jang et al, 2013b). Therefore, to test this hypothesis, we investigated possible associations between genetic variations at the -2578A > C, + 936C > T, and -460C > T polymorphic site in the VEGF gene, in patients who have had CRC compared to healthy individuals.…”
Section: Introductionmentioning
confidence: 98%
“…However, the functional effect of VEGF -634C>G is contested. Watson et al (15) and Hansen et al (38) proposed that the VEGF -634C allele was associated with the decreased production of VEGF, whereas Wongpiyabovorn et al (16) and Awata et al (39) reported that the VEGF -634G allele was associated with decreased VEGF production. These conflicting results are potentially due to the effect of haplotype combinations.…”
Section: Discussionmentioning
confidence: 99%
“…The VEGF promoter SNP À2578 A/C (rs699947) influence the VEGF expression resulting in decreased VEGF serum levels for the AA genotype. For the SNP À460 C/T a lowered VEGF production for carriers of the T-allele and the À1154 G-allele respectively was observed [19,40]. For the SNP +405 C/G the highest VEGF production was observed for the GG genotype [19].…”
Section: Epidemiologymentioning
confidence: 77%
“…ASF1 and Srp49) and a small upstream open reading frame leading to diverse isoforms with differing bioavailability and activities [9,38]. Most isoforms, differing in their pro-or antiangiogenic properties, are mainly generated by alternative splicing of the exons 5-7 and are termed by the amino acid numbers attached [12,39,40].…”
Section: Post-transcriptional Regulationmentioning
confidence: 99%